Исследование свойств рентгеноконтрастного кальцийбарийалюмосиликатного цемента - Цапко, Наталия Сергеевна (НТУ "ХПИ", 2014)
Статья посвящена проблеме разработки отечественного рентгеноконтрастного цемента для нужд стоматологии. Рассмотрена возможность получения такого цемента на основе алюмината кальция и дисиликата бария. Представлены основные этапы синтеза кальцийбарийалюмосиликатного цемента. Подобран рациональный режим помола стеклокристаллического клинкера, для чего было проведено измерение микротвердости по отпечатку алмазной пирамидки на образце – шлифе клинкера. Представлены основные физико-механические и технические свойства разработанного цемента, а также приведены данные специфических стоматологических испытаний. Установлено, что полученный кальцийбарийалюмисиликатный цемент полностью соответствует требованиям, предъявляемым к стоматологическим пломбировочным эндодонтическим материалам.

The article is dedicated to ht problem of the development of domestic radiopaque cement for dentistry needs. The possibility to obtain such cement on the basis of potassium aluminate and barium disilicate has been considered. The main stages of calcium-barium-silica-alumina cement synthesis have been presented. The data as to the clinker structure, obtained with the help of electronic microscopy have been given. It was determined that the obtained clinker consists of a great amount of glass phase which produces crystals of main phases. The efficient mode of grinding has been chosen. For this purpose measurement of microhardness by the dent of a diamond pyramid on the sample - clinker slice - has been conducted. The main physics- mechanical and technical qualities of the developed cement have been presented as well as the data of specific stomatological tests have been given. It was determined that the obtained calcium-barium-silica-alumina cement meets the demands of stomatological filling endodontic materials.
The research of the qualities of radiopaque calcium-barium-silica-alumina cement
Keywords: цемент; стоматология; пломбировочные материалы; клинкер; рентгеноконтрастность; cement; stomatology; filling materials; clinker; radiopacity